Industrial Technologies for CO2 Reduction Applicable to Glass Furnaces - Dario Atzori; Simone Tiozzo; Michela Vellini; Marco Gambini; Stefano Mazzoni (Thermo, 2023)
In recent years, the European Union’s legislation about sustainable development has promoted the gradual decarbonization of all industrial sectors, pushing towards the final goal of a carbon-neutral European glass industry in 2050. Moreover, the COVID-19 pandemic, the war in Ukraine and the consequent natural gas supply crisis have led to significant increases in the costs of traditional energy commodities and CO2 emission allowances. In this scenario, the European glass industry, which is both an energy-intensive sector and a large emitter of CO2, needs to reduce its specific energy consumption, change its energy sources and decarbonize its production process. In order to understand and support this metamorphosis of the glass industry, the follwing questions must be answered: are the technologies reported in scientific publications merely theoretical exercises, or can they be adopted by the industry? In what timeframe can they be adopted? The aim of this study is to review consolidated and emerging technologies applicable to the glass industry and investigate which ones can be implemented in the short or medium term to reduce energy consumption and CO2 emissions related to the glass production process. This study is based on a review of the literature, the materials presented in technical conferences and the opinions of interviewed experts. This study showed that the literature is not very substantial, lacking detailed information on technologies and their effects in terms of energy savings or emissions. More information can be found in the proceedings of selected specialist conferences. This study found that, on one hand, some technologies are mature and only adopted when economically viable, and appropriate boundary conditions are available; the state of the art regarding these technologies was already extensively covered in past publications (e.g., cullet pre-heating). On the other hand, there are many promising technologies in the research or testing phase (i.e., steam methane reforming, process electrification, use of hydrogen); in-depth studies about them are limited due to the novelty of the solutions that they propose or not available due to industrial secrecy issues. In addition to periodicals and specialized conferences, interviews were carried out with managers and technicians from industry, as well as technicians from the Italian glass research institute and industrial machinery producers (especially melting furnaces). The interviews represent added value of this publication, useful in helping us to truly understand the state of the art and degree of readiness of the technologies identified. In addition, the production values of the glass industry were studied: our research confirmed that the most important sub-sectors are flat and container glass, as well as the largest glass-producing nations/continents. Finally, a review of specific energy consumption and CO2 emissions indexes was carried out.